Structural Investigations on Poly(methyl methacrylate) Various Composites Used for Stereolithographyc Complete Dentures - Totu, Eugenia Eftimie; Cristache, Corina Marilena; Isildak, Selim; Tavukcuoglu, Ozlem; Pantazi, Aida; Enachescu, Marius; Buga, Roxana; Burlibasa, Mihai; Totu, Tiberiu (REVISTA CHIMIE SRL, 2018)
The present paper is focused on analyzing if appropriate adhesion between the polymeric matrix and titania filler nanoparticles is obtained for the PMMA-TiO2 photo-curable dental material, suitable for application in RP - stereolithography (SLA) for complete denture manufacturing. It was found that different amounts, between 0.2% and 2.5 % (w/w%), of added titanium oxide nanoparticles slightly modify the structural behavior of the PMMA polymeric matrix. The material characterization was carried out using FT-IR and microscopy techniques.
Keywords: PMMA - TiO2 functionalized nanocomposite; structural analysis; stereolithography; complete denture; MANDIBULAR OVERDENTURE.; ATTACHMENT SYSTEMS; NANOCOMPOSITES; Materials Science